РОЛЬ И ФУНКЦИЯ КОМПЬЮТЕРНЫХ ТЕХНОЛОГИЙ В ЯЗЫКОВОМ ОБРАЗОВАНИИ («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article discusses the use of modern information and communication technologies in teaching language disciplines at the university. Information competence, which has become one of the main indicators of quality education, is one of the main conditions of modern education, and its formation directly depends on the active activity of students in an open information and educational environment.Modern IT makes it possible to create unique didactic conditions for the development and ordering of individual educational trajectories in teaching language disciplines at the university. The paper analyzes the scientific and pedagogical literature on the use of IT tools for language learning. The analysis showed that the main technological features of ICT tools that have opened up wide opportunities for the use of information and communication technologies for the formation and development of foreign language communicative competence are interactivity, multimedia, publicity and hypertext structure.
Keywords: informatization of education, information technologies, language and speech competencies, information competence, computer literacy.